Computer crimes on the COVID-19 scene: analysis of social, legal, and criminal threats - Bokovnya, Alexandra Yuryevna; Khisamova, Zarina Ilduzovna; Rustamovich Begishev, Ildar; Yuryevna Latypova, Elvira; Vladimirovna Nechaeva, Elena (Cuestiones Políticas, 2020)
In January 2020, the World Health Organization announced an outbreak of SARS-CoV2, which caused COVID-19 coronavirus disease. Soon, a continuous outbreak of coronavirus infection was declared a pandemic. This situation has led to an increase in cybercrime. Cybercriminals did not stray from the situation and used the pandemic to commit various digital frauds and cyberattacks. As a result, the objective of the investigation was to analyze computer crimes at the COVID-19 scene and identify their social and legal consequences. This is a documentary-based investigation. It is concluded that, security standards have deteriorated in the context of forty social as many organizations were not prepared for remote work and the number of victims of cybercrime will only grow soon. International organizations and law enforcement agencies in many countries issue many recommendations to prevent digital criminal acts against businesses and citizens. This situation also prompted active legislation around the world to deal with the crisis. Most of the rules adopted in recent months are likely to be derogated.